Nonlinear Dynamical Systems with Applications - Zeng, Shengda; Migórski, Stanisław; Liu, Yongjian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue contains eleven accepted and published submissions to a Special Issue of the MDPI journal Axioms on the subject of "Nonlinear Dynamical Systems with Applications". In this volume, the invited authors have submitted their latest results on nonlinear dynamical systems and related applications. All papers have been accepted after a rigorous review process.